Short-term Treatment of RAW264.7 Macrophages with Adiponectin Increases Tumor Necrosis Factor-α (TNF-α) Expression via ERK1/2 Activation and Egr-1 Expression: ROLE OF TNF-α IN ADIPONECTIN-STIMULATED INTERLEUKIN-10 PRODUCTION - Park, Pil-hoon (2007)
Adiponectin is an adipokine with potent anti-inflammatory properties. However, the mechanisms by which adiponectin suppresses macrophage function are not well understood. Treatment of RAW264.7 macrophages with adiponectin for 18 h decreased lipopolysaccharide (LPS)-stimulated tumor necrosis factor-α (TNF-α) production. Here we demonstrate that globular adiponectin (gAcrp) initially increased TNF-α expression in RAW264.7 macrophages; this TNF-α then contributed to increased expression of interleukin-10, which in turn was required for the development of tolerance to subsequent LPS exposure. gAcrp-mediated increases in TNF-α mRNA accumulation were associated with increased TNF-α promoter activity. gAcrp increased the DNA binding activity of both Egr-1 and NFκB; mutation of either the Egr-1 or NFκB binding sites in the TNF-α promoter decreased gAcrp-stimulated promoter activity. Further, co-transfection with either dominant negative Egr-1 or the IκB super-repressor prevented gAcrp-stimulated TNF-α promoter activity. gAcrp also increased Egr-1 promoter activity, mRNA accumulation, and DNA binding activity. Inhibition of ERK1/2 with U0126 potently suppressed gAcrp-stimulated Egr-1 promoter activity, as well as TNF-α promoter activity. In summary, these data demonstrate that adiponectin initially increases TNF-α production by macrophages via ERK1/2→Egr-1 and NFκB-dependent mechanisms; these increases in TNF-α in turn lead to increased expression of interleukin-10 and an eventual dampening of LPS-mediated cytokine production in macrophages.